Adherence of wild-type and mutant strains of Vibrio cholerae to normal and immune intestinal tissue - Bhattacharjee, J. W. (1979)
Adherence of some wild-type and mutant strains of Vibrio cholerae was studied and the relation between adherence, motility, multiplication, and virulence was examined. Vibrios adhered readily to freshly isolated tissue segments of rabbit intestine at 37°C. The number of vibrios adhering was dependent on the concentration of bacteria to which the tissue was exposed. Adherence was markedly reduced by pretreatment with chloramphenicol and also when intestinal tissue was taken from parenterally or orally immunized rabbits. Non-motile or feebly motile strains were unable to adhere. One motile strain was also found to adhere poorly. The adherence of non-motile or poorly adhering strains was not affected by chloramphenicol. Non-motile, poorly adhering, or slow-growing strains behaved as attenuated strains, suggesting the role of motility, adherence, and multiplication in the virulence of V. cholerae.